"Britain's Own Muslim Polymath:" On the Politics of Representing Ziauddin Sardar. Issue 2 (19th May 2022) - Lal, Vinay
Abstract: This essay seeks to unravel the cultural politics that underpin the approbation of Ziauddin Sardar, one accepted by the author himself, as "Britain's own Muslim polymath." It explores how Sardar models himself after the Muslim polymaths of Islam's "Golden Age, " dwelling on the importance of knowledge and travel in the worldview of Muslim intellectuals. But it also points to the implied anomalousness of the idea of a Muslim polymath, the difficulties that inhere in the idea of multiculturalism, and the necessary ambivalence with which a Muslim intellectual such as Sardar must negotiate the shortcomings of contemporary Islam and multiculturalism alike.